Synopsis of Genetically modified crops in Africa: Economic and policy lessons from countries south of the Sahara - Falck-Zepeda, José B.; Gruère, Guillaume P.; Sithole-Niang, Idah (International Food Policy Research Institute, 2013)
Agriculture has a crucial role to play in ending hunger and poverty in Africa, as it contributes approximately 35 percent of the continent’s gross domestic product while accounting for 70 percent of its labor force. Raising agricultural productivity is one of the best ways to increase rural income, and one promising but controversial means of increasing agricultural productivity is biotechnology, including genetically modified (GM) crops and other organisms.